2018
DOI: 10.1021/acs.jpcb.7b12455
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Features in Cholinium-Based Protic Ionic Liquids from Molecular Dynamics Simulations

Abstract: We explore the structure of a series of protic Ionic Liquids based on the choline cation and amino acid anions. In the series, the length and the branching of the amino acid alkyl chain varies. Ab initio molecular dynamics, X-ray diffraction measurements, and infrared spectra have been used to provide a reliable picture of the short-range structure and of the short-time dynamic process that characterize the fluids. We have put special emphasis on the peculiar and complicated network of hydrogen bonds that stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…In the first investigation, Benedetto et al (Benedetto et al 2014) described in detail the cation-anion interaction with DFT methods in vacuo and in small clusters containing up to four ion pairs, for eight amino acid anions (Ala, Val, Ser, Cys, Asp, Asn, Phe, His). In some later reports (Campetella et al 2015a(Campetella et al , b, 2016a(Campetella et al , b, c, 2017(Campetella et al , 2018, the presence of strong ion pairing was confirmed in larger models of the liquid phase (32 ion pairs). In one of these studies on cholinealanine (Campetella et al 2015a(Campetella et al , 2015b, infrared spectroscopy was chosen as experimental technique to support the computational results.…”
Section: Structural Featuresmentioning
confidence: 75%
“…In the first investigation, Benedetto et al (Benedetto et al 2014) described in detail the cation-anion interaction with DFT methods in vacuo and in small clusters containing up to four ion pairs, for eight amino acid anions (Ala, Val, Ser, Cys, Asp, Asn, Phe, His). In some later reports (Campetella et al 2015a(Campetella et al , b, 2016a(Campetella et al , b, c, 2017(Campetella et al , 2018, the presence of strong ion pairing was confirmed in larger models of the liquid phase (32 ion pairs). In one of these studies on cholinealanine (Campetella et al 2015a(Campetella et al , 2015b, infrared spectroscopy was chosen as experimental technique to support the computational results.…”
Section: Structural Featuresmentioning
confidence: 75%
“…In the series of compounds that we shall present here, the clustering seems to take place between anions where, as we shall see, the cooperative effect of hydrogen bonds is sufficient to overcome the Coulomb repulsion. Here, we try to unravel the basic physics behind this surprising organization pattern that we have already proven to exist for some of the cholinium amino acid-based PILs (e.g., ref (11)).…”
Section: Introductionmentioning
confidence: 96%
“…A more extensive investigation of the structure and vibrational signatures of protic ILs has been presented very recently . The authors selected a series of ILs based on the choline cation and various aminoacid anions, with varying alkyl chain length and ramification: valine (Val − ), norvaline (Nva − ), leucine (Leu − ), and norleucine (Nle − ).…”
Section: Computational Vibrational Spectroscopymentioning
confidence: 99%
“…Top panels, experimental data; second row, global power spectra and carboxyl oxygen; third row, C─H groups. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Computational Vibrational Spectroscopymentioning
confidence: 99%